2017
DOI: 10.3758/s13420-017-0305-y
|View full text |Cite
|
Sign up to set email alerts
|

The rewarding effects of number and surface area of food in rats

Abstract: Visual cues have an important role in food preference for both rats and humans. Here, we aim to isolate the effects of numerosity, density, and surface area on food preference and running speed in rats, by using a forced-choice maze paradigm. In Experiment 1, rats preferred and ran faster for a group of multiple smaller pellets rather than a single large pellet, corroborating previous research (Capaldi, Miller, & Alptekin Journal of Experimental Psychology: Animal Behavior Processes, 15(1), 75-80, 1989). Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 86 publications
2
11
0
Order By: Relevance
“…Food-choice behavior and the impact of visual cues regarding quantity have been the topic of experimental study in a variety of species. For example, rats ( Rattus norvegicus domesticus ) have been shown to prefer multiple smaller pieces of food relative to the same or sometimes even greater amounts of food presented in one large clump, as demonstrated in both choice and running speed data (e.g., Capaldi, Miller, & Alptekin, 1989; Wadhera, Wilkie, & Capaldi-Phillips, 2018). These results differ from primate studies, in which chimpanzees ( Pan troglodytes ) are biased to choose food sets containing the largest individual food item even if choosing that set leads to an overall lesser amount of food (e.g., Beran, Evans, & Harris, 2008; Boysen & Berntson, 1995; Boysen, Berntson, & Mukobi, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Food-choice behavior and the impact of visual cues regarding quantity have been the topic of experimental study in a variety of species. For example, rats ( Rattus norvegicus domesticus ) have been shown to prefer multiple smaller pieces of food relative to the same or sometimes even greater amounts of food presented in one large clump, as demonstrated in both choice and running speed data (e.g., Capaldi, Miller, & Alptekin, 1989; Wadhera, Wilkie, & Capaldi-Phillips, 2018). These results differ from primate studies, in which chimpanzees ( Pan troglodytes ) are biased to choose food sets containing the largest individual food item even if choosing that set leads to an overall lesser amount of food (e.g., Beran, Evans, & Harris, 2008; Boysen & Berntson, 1995; Boysen, Berntson, & Mukobi, 2001).…”
mentioning
confidence: 99%
“…These results differ from primate studies, in which chimpanzees ( Pan troglodytes ) are biased to choose food sets containing the largest individual food item even if choosing that set leads to an overall lesser amount of food (e.g., Beran, Evans, & Harris, 2008; Boysen & Berntson, 1995; Boysen, Berntson, & Mukobi, 2001). Wadhera et al (2018) discussed the role of processing and handling time, suggesting that a preference for multiple smaller food items may in fact be the optimal choice for rodents in the face of competition with conspecifics or potential predation during foraging (see also Bánszegi, Urrutia, Szenczi, & Hudson, 2016, for experimental data with domestic cats). In contrast, chimpanzees may be better able to monopolize a larger food source, leading to an opposite bias for great apes.…”
mentioning
confidence: 99%
“…For rats it was shown that external stimuli (spatial cues) seem to be more important for alternation than proprioceptive cues, i.e., the body's turning response to the left or right (non-spatial cues) (Montgomery 1952). A maze rich of spatial extramaze cues reinforces alternation (Lennartz 2008) but spatial intramaze cues (e.g., patterns on the arm walls) have stronger influence on alternation than extramaze cues (Walker et al 1955). In mice, however, influence of spatial and non-spatial cues seems to differ between strains.…”
Section: Influences On Spontaneous Alternationmentioning
confidence: 99%
“…In a modification of the discrimination test, the T-maze can also be used as a preference test: The arms are provided with different goods, and the animal is required to choose between them. This form of preference test seems to be easily performed with a variety of animal species (mice: Cutuli et al 2015; Correa et al 2015; Roder et al 1996; wild mice: Nunes et al 2009; rats: Leenaars et al 2019; Ras et al 2002; Patterson-Kane et al 2001; van der Plasse et al 2007; Denk et al 2004; Hernandez-Lallement et al 2015; Wadhera et al 2017; Cunningham et al 2015; pigs: Rooijen and Metz 1987; hens: Dawkins 1977; broilers: Buckley et al 2011; zebrafish: Hieu et al 2020; fruit flies: Fujita and Tanimura 2011). Preference is usually assessed by offering the goods in the choice arms of the maze but in some cases, it might be useful to use stimuli which are associated with the to-be-tested goods instead, e.g., in tests for social preference, the real mouse might be replaced by urinary stimuli (Nunes et al 2009; compare also Fitchett et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In a modification of the discrimination test, the T-maze is also used as a preference test: The arms are provided with different goods, and the animal is required to choose between them. This form of preference test seems to be easily performed with a variety of animal species (mice: Roder et al, 1996;Correa et al, 2015;Cutuli et al, 2015;wild mice: Nunes et al, 2009;rats: Patterson-Kane et al, 2001;Ras et al, 2002;Denk et al, 2004;van der Plasse et al, 2007;Cunningham et al, 2015;Hernandez-Lallement et al, 2015;Wadhera et al, 2017;Leenaars et al, 2019;pigs: Rooijen & Metz, 1987;hens: Dawkins, 1977;broilers: Buckley et al, 2011;zebrafish: Hieu et al, 2020; fruit flies: Fujita & Tanimura, 2011). Preference is usually assessed by offering the goods in the choice arms of the maze but in some cases, it might be useful to use stimuli which are associated with the to-be-tested goods instead, e.g., in tests for social preference, the real mouse might be replaced by urinary stimuli (Nunes et al, 2009; compare also Fitchett et al, 2006).…”
Section: Introductionmentioning
confidence: 99%